2014
DOI: 10.1358/dot.2014.50.11.2232267
|View full text |Cite
|
Sign up to set email alerts
|

Tofogliflozin: A highly selective SGLT2 inhibitor for the treatment of type 2 diabetes

Abstract: Diabetes mellitus impacts a substantial number of people worldwide and despite numerous antidiabetic medications available, approximately half of the drugs do not attain their recommended target, glycated hemoglobin (HbA1c). Recently, the kidney and its role in glucose reabsorption through the sodium/glucose cotransporter 2 (SGLT2) has been the target for novel antidiabetic treatments. Pharmacologic inhibition of SGLT2 in patients with diabetes results in increased urinary glucose excretion and decreased blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Data from clinical studies have demonstrated that oral administration of SGLT2 inhibitors induces UGE, improves hyperglycemia, and reduces the body weight of patients with T2D [5][6][7]. These SGLT2 inhibitors were developed based on the structure of phlorizin [8].…”
Section: Safety and Tolerability Of The Sglt2 Inhibitor Empagliflozinmentioning
confidence: 99%
“…Data from clinical studies have demonstrated that oral administration of SGLT2 inhibitors induces UGE, improves hyperglycemia, and reduces the body weight of patients with T2D [5][6][7]. These SGLT2 inhibitors were developed based on the structure of phlorizin [8].…”
Section: Safety and Tolerability Of The Sglt2 Inhibitor Empagliflozinmentioning
confidence: 99%
“…Tofogliflozin is a potent and highly selective sodium–glucose cotransporter 2 (SGLT2) inhibitor, and is currently used for the treatment of patients with type 2 diabetes mellitus in Japan. SGLT2 inhibitors exert their antidiabetic effects by inhibiting SGLT2, which is localized in the proximal renal tubule and is responsible for approximately 90% of glucose reabsorption in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Tofogliflozin is a potent and highly selective sodium-glucose cotransporter 2 (SGLT2) inhibitor [1][2][3] , and is currently used for reabsorption and an increase in urinary glucose excretion results in decreased blood glucose levels 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of renal glucose reabsorption and an increase in urinary glucose excretion results in decreased blood glucose levels in an insulin‐independent manner. Tofogliflozin is a potent and highly selective SGLT2 inhibitor with a 2,900‐fold selectivity for SGLT2 over SGLT1. Tofogliflozin was approved in Japan in 2014 for the treatment of type 2 diabetes mellitus as monotherapy or in combination with other antidiabetic agents.…”
Section: Introductionmentioning
confidence: 99%